Evaluasi Pemanfaatan Online Compiler dan Autograder Sebagai Pendukung Aktivitasi Praktikum Pemograman Mahasiswa - Muhammad Galih Wonoseto; Muhammad Jibril (UIN Sunan Kalijaga Yogyakarta, 2026)
The automation of programming practicum assessment using an online compiler has become increasingly important to address the limitations of manual evaluation, such as time inefficiency, subjectivity, and the lack of automated feedback support in conventional e-learning systems. This study aims to evaluate the implementation of an online compiler and autograder in a programming practicum through interviews and questionnaires with 91 respondents, comprising lecturers and students. The online compiler and autograder were implemented using the Moodle platform, integrated with the CodeRunner plugin and the JOBE server to automate code evaluation and provide real-time feedback to students. User acceptance was assessed using the Technology Acceptance Model (TAM), which includes three dimensions: perceived ease of use, perceived usefulness, and system acceptance. The evaluation results indicate positive scores across all dimensions, with 78.75% for ease of use, 78.09% for usefulness, and 76.33% for system acceptance. These findings demonstrate that the proposed system effectively improves the assessment process and shows strong potential for adoption in programming education environments.